Clinical thyroidology: beyond the 1970s’ TSH-T4 Paradigm - Lindner, Henry H. (Frontiers in Endocrinology, 2025)
The 2012 American endocrine associations' guidelines on hypothyroidism were a reiteration of the TSH-T4 Paradigm from the 1970s. They likewise defined hypothyroidism as hypothyroxinemia, assumed that almost all hypothyroidism was primary, and relied upon the thyroid stimulating hormone (TSH) test and inactive prohormone thyroxine (T4) for diagnosis and treatment. The guidelines’ authors acknowledged many TSH and other “pitfalls” in the paradigm yet warned physicians against attending to patients’ signs and symptoms and relative free T4 (FT4) and free triiodothyronine (FT3) levels—the only means by which to identify and avoid all pitfalls and provide individualized diagnosis and treatment. This inadequate paradigm has distorted medical practice and research for 50 years, including laboratories’ FT4 and FT3 reference ranges. It produces overdiagnosis, underdiagnosis, inadequate treatment, and widespread patient dissatisfaction. Since the 1970s, our understanding of thyroid hormone production, transport, metabolism, reception, and signaling has increased greatly, as has our appreciation of the importance of optimal T3 effects for health and wellbeing. Hypothyroidism must be defined physiologically as insufficient T3 effect in some or all tissues. The best indicators of tissue T3 effect are the patient’s signs and symptoms, and the best serum tests are FT4 and FT3, considered together. The TSH level is not a reliable indicator of T3 status in the untreated state and is oversuppressed by the peak levels that occur with once-daily oral T4 and/or T3. Normalizing an elevated TSH or low FT4 with T4 usually does not produce sufficient, let alone optimal, T3 effect and can leave some patients markedly hypothyroid. T4/T3 combination therapy is more physiological and effective than T4 monotherapy and must be guided by clinical criteria, not the TSH. Some patients cannot tolerate more T3 effect due to hypocortisolism, inflammation, and other disorders. There is no substitute for the practice of fully informed clinical medicine.